2021
DOI: 10.1111/all.14850
|View full text |Cite
|
Sign up to set email alerts
|

Silencing of SARS‐CoV‐2 with modified siRNA‐peptide dendrimer formulation

Abstract: Background: First vaccines for prevention of Coronavirus disease 2019 (COVID-19) are becoming available but there is a huge and unmet need for specific forms of treatment. In this study we aimed to evaluate the anti-SARS-CoV-2 effect of siRNA both in vitro and in vivo.Methods: To identify the most effective molecule out of a panel of 15 in silico designed siRNAs, an in vitro screening system based on vectors expressing SARS-CoV-2 genes fused with the firefly luciferase reporter gene and SARS-CoV-2-infected cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
77
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 85 publications
(84 citation statements)
references
References 63 publications
1
77
0
6
Order By: Relevance
“…The siRNA-LNPs robustly repressed virus in the lungs and provided a survival advantage to the treated mice [56]. Another recent in vivo study by Khaitov et al demonstrated that topical application by inhalation of a stabilized siRNA modified with a peptide dendrimer targeting the RdRp of SARS-CoV-2 significantly reduced viral load and inflammation in the lung of a Syrian hamster model [57]. Taken together, these are promising results for the development of RNAi-based therapy of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The siRNA-LNPs robustly repressed virus in the lungs and provided a survival advantage to the treated mice [56]. Another recent in vivo study by Khaitov et al demonstrated that topical application by inhalation of a stabilized siRNA modified with a peptide dendrimer targeting the RdRp of SARS-CoV-2 significantly reduced viral load and inflammation in the lung of a Syrian hamster model [57]. Taken together, these are promising results for the development of RNAi-based therapy of COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…For example, nasally applied siRNAs resulted in the highly effective inhibition of respiratory syncytial virus (RSV) and SARS-CoV-1 in animal models [44,67,68]. Nebulizers or inhalers were developed to generate aerosols for drug delivery by inhalation directly to the lung [69] as recently successfully implemented for SARS-CoV-2 inhibition [57]. Administration of an siRNA targeting the RSV N gene (ALN-RSV01) by inhalation for the potential treatment or prevention of RSV infection was also investigated in a clinical study.…”
Section: Discussionmentioning
confidence: 99%
“…The study reported marked repression of virus in the lungs and pronounced survival advantage to the treated mice. Khaitov et al selected a siRNA against the viral RdRp out of 15 in-silico designed siRNAs as the most efficient siRNA inhibiting viral replication in vitro ( Khaitov et al, 2021 ). Moreover, they showed that locked nucleic acids (LNAs) modification increases the RNA stability and complexation with the designed peptide dendrimer (KK-46) enhances cellular uptake to allow topical application by inhalation of the final formulation.…”
Section: Sirnas and Their Therapeutic Potentials Against Covid-19mentioning
confidence: 99%
“…These dendrimers proved to be a basis for further research as an antiviral therapy [ 103 ]. Recent studies also showed that topical application by inhalation of peptide dendrimer carrying SARS-CoV-2-specific modified siRNA can potentially be used for the treatment of SARS-CoV-2-induced lung inflammation [ 104 ].…”
Section: Application Of Dendrimers In Treatment Of Infectious Diseasesmentioning
confidence: 99%